Surface treatment method for rolled copper foil
Through pickling, roughening, curing, heat resistance, anti-oxidation and plasma treatment, combined with the coating of epoxy resin and silane coupling agent, the problem of difficult to take into account both the peel strength and the surface roughness of the rolled copper foil, and the effect of high peel strength and low roughness is achieved.
Patent Information
- Application Number
- CN202411822417.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, it is difficult to take into account the problems of high peel strength and low surface roughness.
Through pickling, roughening treatment, curing treatment, heat-resistant treatment, anti-oxidation treatment and plasma treatment, an appropriate amount of copper buds and anti-oxidation film is formed, and the surface is coated with epoxy resin and silane coupling agent to enhance the binding force of the copper foil and the resin.
It is achieved to improve the peel strength and corrosion resistance of the rolled copper foil without increasing the surface roughness, and meet the requirements of high-frequency and high-speed signal transmission.
Smart Images

Figure CN119702403A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rolled copper foil, and in particular to a surface treatment method of rolled copper foil. Background Art
[0002] With the rapid development of 5G mobile communication technology, signal frequency and transmission speed are constantly increasing. High-frequency and high-speed signals are prone to significant skin effect during transmission on circuit boards with excessively high surface roughness, which can cause transmission signal attenuation and distortion. Therefore, it is particularly urgent to reduce the surface roughness of rolled copper foil used in printed circuit boards (FPCs). At the same time, it is also necessary to ensure that other mechanical properties of the copper foil, such as peel strength, meet the requirements of the FPC manufacturing process. In response to the application requirements of high-speed and high-frequency transmission lines, the development of rolled copper foil with both appropriate roughness and high peel strength is the key to the development of future high-end products.
[0003] In the production process of rolled copper foil, peel strength is a key performance indicator, which directly affects the quality of electronic products and the stability of the production process. The improvement of peel strength is of great significance to improving the reliability and durability of circuit boards. At present, in order to improve the peel strength of rolled copper foil, the industry has adopted a variety of technical solutions. In order to ensure that there is sufficient bonding force between the rolled copper foil and the resin substrate of the printed circuit board, surface roughening treatment must be performed. The essence of roughening treatment is to electroplate a layer of nodular copper particles on the surface of the rolled copper foil to increase the surface roughness of the rolled copper foil, thereby enhancing the bonding force with the resin substrate. Although the bonding force between the rolled copper foil and the resin substrate of the printed circuit board after such treatment is relatively high, it cannot meet the requirements of low surface roughness for high-frequency and high-speed signal transmission.
[0004] The surface treatment steps of rolled copper foil involve: degreasing - pickling - roughening - curing - heat resistant treatment - anti-oxidation treatment - silane coupling agent - drying. The traditional method of improving the peel strength of surface treated rolled copper foil is to physically enhance the peel strength by producing larger copper buds on the surface of the copper foil through multiple roughening and curing steps (often requiring two to three roughenings and two to three curings). However, multiple roughening and curing will increase the surface roughness of the copper foil, and the roughness Rz is greater than 2μm. Increased roughness will cause signal loss on the circuit board due to the skin effect. In addition, multiple steps such as roughening and curing result in a long production process and low production efficiency. Summary of the invention
[0005] The main purpose of the present invention is to provide a surface treatment method for a rolled copper foil, so as to solve the problem in the prior art that it is difficult to achieve both high peel strength and low surface roughness of the rolled copper foil.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a surface treatment method for a rolled copper foil is provided, and the surface treatment method comprises: step S1, sequentially subjecting the rolled copper foil to pickling, roughening treatment, curing treatment, heat resistance treatment, anti-oxidation treatment, and plasma treatment; sequentially subjecting the plasma-treated rolled copper foil to silane coupling agent solution coating and first curing to obtain a pre-treated rolled copper foil; step S2, sequentially subjecting the pre-treated rolled copper foil to epoxy resin solution coating, curing agent solution coating, and second curing to obtain a surface-treated rolled copper foil; wherein the mass concentration of the epoxy resin in the epoxy resin solution does not exceed 10wt%.
[0007] Furthermore, the ratio of the mass of epoxy resin in the epoxy resin solution applied to the surface area of the rolled copper foil is 0.03-0.3 g: 60 cm 2 ; and / or, the ratio of the mass of epoxy resin in the coated epoxy resin solution to the mass of the curing agent in the curing agent solution is 10:1; preferably, the epoxy resin solution is a dimer acid-modified epoxy resin solution or a diphenylmethane diisocyanate-modified epoxy resin solution; and / or, the curing agent solution is a triethylenetetramine solution or a diethylenetriamine solution.
[0008] Furthermore, the mass concentration of the epoxy resin in the epoxy resin solution is 2 to 10 wt %; and / or the mass concentration of the curing agent in the curing agent solution is 2 to 10 wt %;
[0009] Furthermore, the power of the above-mentioned plasma treatment is 10 to 100 W; and / or the time of the plasma treatment is 10 to 60 s; and / or the gas for the plasma treatment is an oxygen-containing gas; preferably, the oxygen-containing gas is an Ar / O2 mixed gas or air; further preferably, the volume ratio of argon to oxygen in the Ar / O2 mixed gas is 5 to 9:1.
[0010] Furthermore, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.1-1 wt%; and / or the ratio of the mass of the silane coupling agent in the coated silane coupling agent solution to the surface area of the rolled copper foil is 0.0015-0.03 g:60 cm 2 ; and / or, the pH value of the silane coupling agent solution is 3-5; and / or, the silane coupling agent is selected from any one or more of glycidyloxypropyl trimethoxysilane, aminopropyl triethoxysilane, 3-(trimethoxymethylsilyl) propyl methacrylate and (3-mercaptopropyl) trimethoxysilane; preferably, the silane coupling agent is a combination of glycidyloxypropyl trimethoxysilane and aminopropyl triethoxysilane, and the mass ratio of glycidyloxypropyl trimethoxysilane to aminopropyl triethoxysilane is 0.1-1:0.1-1; and / or, the solvent in the silane coupling agent solution is a mixture of ethanol and water, and the volume ratio of ethanol to water is 2-5:1.
[0011] Furthermore, the pickling includes: immersing the rolled copper foil in a sulfuric acid solution to obtain the pickled rolled copper foil; and / or the volume concentration of sulfuric acid in the sulfuric acid solution is 10-15%; and / or the immersion temperature is 20-30°C; and / or the immersion time is 10-30s.
[0012] Furthermore, the roughening treatment includes: placing the pickled rolled copper foil in a roughening tank containing a roughening solution for a first electrodeposition to obtain the roughened rolled copper foil; and / or the current density of the first electrodeposition is 20 to 50 A / dm 2 ; and / or, the temperature of the first electrodeposition is 25 to 30°C; and / or, the time of the first electrodeposition is 3 to 10 seconds; and / or, the roughening solution is a mixture of copper sulfate and sulfuric acid, and the roughening solution contains Cu 2+ The concentration of H2SO4 in the roughening solution is 10-30 g / L; and / or the concentration of H2SO4 in the roughening solution is 100-200 g / L.
[0013] Furthermore, the curing treatment comprises: placing the roughened rolled copper foil in a curing tank containing a curing liquid for a second electrodeposition to obtain the cured rolled copper foil; and / or the current density of the second electrodeposition is 10 to 40 A / dm 2 ; and / or, the temperature of the second electrodeposition is 30 to 60°C; and / or, the time of the second electrodeposition is 3 to 10 seconds; and / or, the solidifying liquid is a mixture of copper sulfate and sulfuric acid, and the solidifying liquid contains Cu 2+ The concentration of H2SO4 in the solidifying liquid is 30-60 g / L; and / or the concentration of H2SO4 in the solidifying liquid is 100-200 g / L.
[0014] Furthermore, the heat-resistant treatment comprises: placing the rolled copper foil after the curing treatment in a heat-resistant tank containing a heat-resistant liquid for a third electrodeposition to obtain the rolled copper foil after the heat-resistant treatment; and / or the current density of the third electrodeposition is 1 to 3 A / dm 2 ; and / or, the temperature of the third electrodeposition is 30-50°C; and / or, the time of the third electrodeposition is 3-10s; and / or, the heat-resistant liquid is a mixture of potassium pyrophosphate and zinc sulfate, and the concentration of K4P2O7 in the heat-resistant liquid is 40-200g / L; and / or, the Zn in the heat-resistant liquid 2+ The concentration is 1 to 5 g / L; and / or the pH value of the heat-resistant liquid is 8 to 11; and / or the anti-oxidation treatment comprises: placing the rolled copper foil after the heat-resistant treatment in an anti-oxidation tank containing an anti-oxidation liquid for a fourth electrodeposition to obtain the rolled copper foil after the anti-oxidation treatment; and / or the current density of the fourth electrodeposition is 3 to 10 A / dm 2; and / or, the temperature of the fourth electrodeposition is 25 to 35°C; and / or, the time of the fourth electrodeposition is 3 to 10s; and / or, the anti-oxidation liquid is a mixture of potassium dichromate and potassium hydroxide, and the concentration of chromium ions in the anti-oxidation liquid is 1 to 10g / L; and / or, the pH value of the anti-oxidation liquid is 10 to 13.
[0015] Furthermore, the above-mentioned second curing includes hot air drying and vacuum drying performed in sequence; and / or, the temperature of hot air drying is 150-200°C; and / or, the time of hot air drying is 10-60s; and / or, the temperature of vacuum drying is 100-150°C; and / or, the time of vacuum drying is 6-12h.
[0016] By applying the technical scheme of the present invention, the present application removes the oxide on the surface of the rolled copper foil by pickling the rolled copper foil. The copper buds grow and stably exist on the surface of the copper foil by roughening treatment and curing treatment. The zinc coating is formed on the surface of the copper layer by heat-resistant treatment, which helps to block the thermal diffusion of copper ions and epoxy resin during heat treatment and improve the corrosion resistance of the rolled copper foil. The anti-oxidation treatment forms a chromium-containing antioxidant film on the surface of the zinc coating, which helps to improve the corrosion resistance and oxidation resistance of the rolled copper foil. The plasma surface treatment increases the active oxygen-containing functional groups on the surface of the rolled copper foil, which helps to improve the interaction between the silanol group and the oxygen-containing functional group of the silane coupling agent after hydrolysis, thereby helping to improve the bonding force between the rolled copper foil and the epoxy resin, and further helps to improve the peel strength of the rolled copper foil. At the same time, the plasma surface treatment helps to increase the surface energy of the rolled copper foil and improve the spreading and infiltration of the silane coupling agent treatment solution in the pores of the copper buds. Coating the epoxy resin solution on the surface of the pre-treated rolled copper foil and controlling the mass concentration of the epoxy resin in the epoxy resin solution within the above range helps to pre-fill the epoxy resin solution between the copper bud particles, enhance the penetration of the epoxy resin between the copper bud particles, increase the contact area between the epoxy resin and the copper bud, and increase the peel strength of the rolled copper foil through mechanical interlocking between the epoxy resin and the copper bud particles. At the same time, the hydrophobic end of the silane coupling agent and the epoxy resin molecules are entangled with each other, which helps to enhance the interaction force between the molecules, thereby helping to further enhance the peel strength of the rolled copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 The SEM image of the surface treated rolled copper foil in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] As analyzed in the background technology of this application, in the prior art, it is difficult to achieve both high peel strength and low surface roughness for rolled copper foil. In order to solve the above problem, this application provides a surface treatment method for rolled copper foil.
[0021] In a typical embodiment of the present application, a surface treatment method for a rolled copper foil is provided, and the surface treatment method comprises: step S1, sequentially subjecting the rolled copper foil to pickling, roughening treatment, curing treatment, heat resistance treatment, anti-oxidation treatment, and plasma treatment; sequentially subjecting the plasma-treated rolled copper foil to silane coupling agent solution coating and first curing to obtain a pretreated rolled copper foil; step S2, sequentially subjecting the pretreated rolled copper foil to epoxy resin solution coating, curing agent solution coating, and second curing to obtain a surface-treated rolled copper foil; wherein the mass concentration of the epoxy resin in the epoxy resin solution does not exceed 10wt%.
[0022] The present application involves pickling the rolled copper foil to remove oxides on the surface of the rolled copper foil. Roughening and curing treatments are performed to achieve the growth and stable existence of copper buds on the surface of the copper foil. Heat-resistant treatment is performed to form a zinc coating on the surface of the copper layer, which helps to block the thermal diffusion of copper ions and epoxy resin during heat treatment and improve the corrosion resistance of the rolled copper foil. Anti-oxidation treatment is performed to form a chromium-containing antioxidant film on the surface of the zinc coating, which helps to improve the corrosion resistance and oxidation resistance of the rolled copper foil. Plasma surface treatment increases the active oxygen-containing functional groups on the surface of the rolled copper foil, which helps to improve the interaction between the silanol groups and oxygen-containing functional groups of the silane coupling agent after hydrolysis, thereby helping to improve the bonding force between the rolled copper foil and the epoxy resin, and further helps to improve the peel strength of the rolled copper foil. At the same time, plasma surface treatment helps to increase the surface energy of the rolled copper foil and improve the spreading and infiltration of the silane coupling agent treatment solution in the pores of the copper buds. Coating the epoxy resin solution on the surface of the pre-treated rolled copper foil and controlling the mass concentration of the epoxy resin in the epoxy resin solution within the above range helps to pre-fill the epoxy resin solution between the copper bud particles, enhance the penetration of the epoxy resin between the copper bud particles, increase the contact area between the epoxy resin and the copper bud, and increase the peel strength of the rolled copper foil through mechanical interlocking between the epoxy resin and the copper bud particles. At the same time, the hydrophobic end of the silane coupling agent and the epoxy resin molecules are entangled with each other, which helps to enhance the interaction force between the molecules, thereby helping to further enhance the peel strength of the rolled copper foil.
[0023] The process of silane coupling agent from bonding to cross-linking:
[0024]
[0025] During the above-mentioned silane coupling agent treatment, the silanol groups of the silane coupling agent react with the oxygen-containing functional groups on the surface of the copper foil to form bonds, and a stable Si-O-Cu chemical bond is formed by heating and dehydration.
[0026] In one embodiment of the present application, the ratio of the mass of epoxy resin in the epoxy resin solution to the surface area of the rolled copper foil is 0.03-0.3 g: 60 cm 2 ; and / or, the ratio of the mass of epoxy resin in the coated epoxy resin solution to the mass of the curing agent in the curing agent solution is 10:1; preferably, the epoxy resin solution is a dimer acid-modified epoxy resin solution or a diphenylmethane diisocyanate-modified epoxy resin solution; and / or, the curing agent solution is a triethylenetetramine solution or a diethylenetriamine solution.
[0027] It is preferred to control the ratio of the mass of epoxy resin in the epoxy resin solution to the surface area of the rolled copper foil within the above range, which helps to control the thickness of the epoxy resin. A coating that is too thin may not be fully penetrated and filled, while a coating that is too thick may increase the surface roughness and affect the signal transmission performance. Controlling the thickness of the epoxy resin within a suitable range helps to reduce the surface roughness of the rolled copper foil while improving the peel strength of the rolled copper foil. It is preferred to control the ratio of the mass of the epoxy resin in the epoxy resin solution to the mass of the curing agent in the curing agent solution to the above value, which helps to improve the curing efficiency of the epoxy resin. It is preferred to control the types of the epoxy resin solution and the curing agent solution within the above range, which helps to further improve the peel strength of the rolled copper foil.
[0028] Including but not limited to, the model of dimer acid modified epoxy resin solution is SQE-172; the model of diphenylmethane diisocyanate solution is SQE-140.
[0029] In one embodiment of the present application, the mass concentration of the epoxy resin in the epoxy resin solution is 2-10 wt %; and / or the mass concentration of the curing agent in the curing agent solution is 2-10 wt %.
[0030] Too low a mass concentration of epoxy resin may lead to insufficient resin filling, while too high a mass concentration of epoxy resin may affect the fluidity and permeability of the resin. It is preferred to control the mass concentration of epoxy resin in the epoxy resin solution within the above range, which helps the epoxy resin to provide enough resin molecules to fill the micropores on the surface of the copper foil and the roughened copper buds, forming a mechanical interlock, thereby helping to improve the peel strength of the rolled copper foil. It is preferred to control the mass concentration of the curing agent within the above range, which helps to improve the curing rate of the epoxy resin.
[0031] In one embodiment of the present application, the solvent in the epoxy resin solution and the solvent in the curing agent solution are each independently selected from any one or more of ethanol, xylene and methyl ethyl ketone; and / or, the coating method of the epoxy resin solution and the curing agent solution is each independently spraying.
[0032] In one embodiment of the present application, the power of the above-mentioned plasma treatment is 10 to 100 W; and / or the time of the plasma treatment is 10 to 60 s; and / or the gas for the plasma treatment is an oxygen-containing gas; preferably, the oxygen-containing gas is an Ar / O2 mixed gas or air; further preferably, the volume ratio of argon to oxygen in the Ar / O2 mixed gas is 5 to 9:1.
[0033] If the power of plasma treatment is too high, the surface of the rolled copper foil may be damaged. If the power of plasma treatment is too low, the activation effect may be insufficient, and the oxygen-containing functional groups on the surface of the rolled copper foil may be too low. It is preferred to control the power of plasma treatment within the above range to help effectively activate the surface of the rolled copper foil, increase the oxygen-containing functional groups on the surface, and provide more reaction sites for subsequent silane coupling agent treatment, thereby helping to enhance the strength of the chemical bond between the epoxy resin and the rolled copper foil. If the time of plasma treatment is too long, it is easy to cause excessive oxidation of the surface. If the time of plasma treatment is too short, it is not conducive to increasing the content of oxygen-containing functional groups on the surface of the rolled copper foil. It is preferred to control the time of plasma treatment within the above range to help improve the efficiency of plasma treatment. It is preferred to control the type of gas for plasma treatment within the above range to help provide sufficient oxygen source while controlling the cost of ion treatment, promote oxidation reaction on the surface of copper foil, and generate oxygen-containing functional groups.
[0034] In one embodiment of the present application, the radio frequency power of the above-mentioned plasma treatment is 13.56 MHz.
[0035] In one embodiment of the present application, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.1-1wt%; and / or the ratio of the mass of the silane coupling agent in the coated silane coupling agent solution to the surface area of the rolled copper foil is 0.0015-0.03g:60cm 2 ; and / or, the pH value of the silane coupling agent solution is 3-5; and / or, the silane coupling agent is selected from any one or more of glycidyloxypropyl trimethoxysilane, aminopropyl triethoxysilane, 3-(trimethoxymethylsilyl) propyl methacrylate and (3-mercaptopropyl) trimethoxysilane; preferably, the silane coupling agent is a combination of glycidyloxypropyl trimethoxysilane and aminopropyl triethoxysilane, and the mass ratio of glycidyloxypropyl trimethoxysilane to aminopropyl triethoxysilane is 0.1-1:0.1-1; and / or, the solvent in the silane coupling agent solution is a mixture of ethanol and water, and the volume ratio of ethanol to water is 2-5:1.
[0036] Preferably, the mass concentration of the silane coupling agent in the silane coupling agent solution is controlled within the above range, which helps to control the distribution density of the silane coupling agent on the surface of the rolled copper foil, thereby helping to improve the uniformity of the distribution of the Si-O-Cu chemical bond. Preferably, the ratio of the mass of the silane coupling agent in the silane coupling agent solution to the surface area of the rolled copper foil is controlled within the above range, which helps to form an appropriate amount of Si-O-Cu chemical bonds, thereby helping to enhance the bonding force between the epoxy resin and the surface of the rolled copper foil. In an acidic environment, the silane coupling agent is hydrolyzed to generate silanol groups. Preferably, the pH value is controlled within the above range, which helps to promote the generation of silanol groups and improve the activity of the silane coupling agent, thereby helping to enhance the chemical bonding ability of the silane coupling agent with the surface of the rolled copper foil. The combined use of glycidyl ether oxypropyl trimethoxy silane and aminopropyl triethoxy silane can enhance the physical and chemical interaction between the silane coupling agent and the resin through the synergistic effect of epoxy ether and amino functional groups, thereby helping to further improve the peel strength of the rolled copper foil. Controlling the mass ratio of glycidyloxypropyl trimethoxysilane and aminopropyl triethoxysilane within the above range can balance the hydrophobicity of epoxy ether and the hydrophilicity of amino group, forming a more stable and optimized coupling layer, thereby helping to enhance the wettability and mechanical interlocking effect of the resin. Water is the medium for the hydrolysis reaction of the silane coupling agent, and the presence of ethanol helps to improve the solubility and stability of the silane coupling agent and promote the hydrolysis reaction. It is preferred to control the volume ratio of ethanol and water within the above range, which helps to improve the stability of the silane coupling agent solution while improving the efficiency of the hydrolysis reaction of the silane coupling agent.
[0037] In one embodiment of the present application, the silane coupling agent solution is applied by spraying; and / or, cold air is used for drying for the first curing, and the temperature of the cold air is 15 to 20° C.; and / or, acetic acid is used to adjust the pH of the silane coupling agent solution.
[0038] In one embodiment of the present application, the above-mentioned pickling includes: immersing the rolled copper foil in a sulfuric acid solution to obtain the pickled rolled copper foil; and / or the volume concentration of sulfuric acid in the sulfuric acid solution is 10 to 15%; and / or the immersion temperature is 20 to 30°C; and / or the immersion time is 10 to 30 seconds.
[0039] It is preferred to control the volume concentration of sulfuric acid in the sulfuric acid solution, the immersion temperature and time within the above ranges, which helps to reduce the corrosion of the rolled copper foil by sulfuric acid and improve the efficiency of removing oxides, oil stains and impurities on the surface of the rolled copper foil.
[0040] In order to control the number of copper buds formed on the surface of the rolled copper foil, improve the peel strength of the rolled copper foil and reduce the roughness of the rolled copper foil, in one embodiment of the present application, the roughening treatment preferably includes: placing the pickled rolled copper foil in a roughening tank containing a roughening liquid for a first electrodeposition to obtain a roughened rolled copper foil; and / or, the current density of the first electrodeposition is 20 to 50 A / dm 2 ; and / or, the temperature of the first electrodeposition is 25 to 30°C; and / or, the time of the first electrodeposition is 3 to 10 seconds; and / or, the roughening solution is a mixture of copper sulfate and sulfuric acid, and the roughening solution contains Cu 2+ The concentration of H2SO4 in the roughening solution is 10-30 g / L; and / or the concentration of H2SO4 in the roughening solution is 100-200 g / L.
[0041] A copper layer is formed on the surface of the copper bud by curing treatment. In order to further improve the stability of the copper bud, in one embodiment of the present application, the curing treatment preferably includes: placing the rolled copper foil after the roughening treatment in a curing tank containing a curing liquid for a second electrodeposition to obtain the rolled copper foil after the curing treatment; and / or, the current density of the second electrodeposition is 10 to 40 A / dm 2 ; and / or, the temperature of the second electrodeposition is 30 to 60°C; and / or, the time of the second electrodeposition is 3 to 10 seconds; and / or, the solidifying liquid is a mixture of copper sulfate and sulfuric acid, and the solidifying liquid contains Cu 2+ The concentration of H2SO4 in the solidifying liquid is 30-60 g / L; and / or the concentration of H2SO4 in the solidifying liquid is 100-200 g / L.
[0042] A zinc plating layer is formed on the surface of the copper layer by heat-resistant treatment. In order to further block the thermal diffusion of copper ions and resin during the heat treatment, in one embodiment of the present application, the heat-resistant treatment preferably includes: placing the rolled copper foil after the curing treatment in a heat-resistant tank containing a heat-resistant liquid for a third electrodeposition to obtain the rolled copper foil after the heat-resistant treatment; and / or, the current density of the third electrodeposition is 1 to 3 A / dm 2 ; and / or, the temperature of the third electrodeposition is 30-50°C; and / or, the time of the third electrodeposition is 3-10s; and / or, the heat-resistant liquid is a mixture of potassium pyrophosphate and zinc sulfate, and the concentration of K4P2O7 in the heat-resistant liquid is 40-200g / L; and / or, the Zn in the heat-resistant liquid 2+ The concentration is 1 to 5 g / L; and / or the pH value of the heat-resistant liquid is 8 to 11.
[0043] A chromium-containing anti-oxidation film is formed on the surface of the zinc coating by anti-oxidation treatment. In order to further improve the corrosion resistance and oxidation resistance of the rolled copper foil, in one embodiment of the present application, the anti-oxidation treatment preferably includes: placing the rolled copper foil after the heat-resistant treatment in an anti-oxidation tank containing an anti-oxidation liquid for a fourth electrodeposition to obtain the rolled copper foil after the anti-oxidation treatment; and / or, the current density of the fourth electrodeposition is 3 to 10 A / dm 2 ; and / or, the temperature of the fourth electrodeposition is 25 to 35°C; and / or, the time of the fourth electrodeposition is 3 to 10s; and / or, the anti-oxidation liquid is a mixture of potassium dichromate and potassium hydroxide, and the concentration of chromium ions in the anti-oxidation liquid is 1 to 10g / L; and / or, the pH value of the anti-oxidation liquid is 10 to 13.
[0044] In one embodiment of the present application, the above-mentioned second curing includes hot air drying and vacuum drying performed in sequence; and / or, the temperature of hot air drying is 150-200°C; and / or, the time of hot air drying is 10-60s; and / or, the temperature of vacuum drying is 100-150°C; and / or, the time of vacuum drying is 6-12h.
[0045] The second curing helps to remove the physically bound water and solvent on the surface of the rolled copper foil, and further removes the chemically bound water between the silanol end and the oxygen-containing functional groups on the surface of the rolled copper foil, forming a chemical bond, which helps to improve the peel strength of the rolled copper foil. Hot air drying helps to remove physically bound water and solvent, and vacuum drying helps to remove the chemically bound water between the silanol and the rolled copper foil, achieving the curing of the silane coupling agent and epoxy resin.
[0046] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0047] Example 1
[0048] The rolled copper foil is placed in a sulfuric acid solution with a volume concentration of 10% and immersed at 30°C for 10 seconds to obtain a pickled rolled copper foil; the pickled rolled copper foil is placed in a roughening tank containing a roughening solution for a first electrodeposition to obtain a roughened rolled copper foil, wherein the current density of the first electrodeposition is 20A / dm 2 The temperature of the first electrodeposition is 25°C, the time of the first electrodeposition is 10s, the roughening solution is a mixture of copper sulfate and sulfuric acid, and the copper in the roughening solution is 2+ The concentration of H2SO4 in the roughening solution is 10 g / L, and the concentration of H2SO4 in the roughening solution is 200 g / L; the rolled copper foil after the roughening treatment is placed in a curing tank containing a curing solution for a second electrodeposition to obtain a rolled copper foil after the curing treatment, and the current density of the second electrodeposition is 10 A / dm 2 The temperature of the second electrodeposition is 60°C, the time of the second electrodeposition is 3s, and the solidifying liquid is a mixture of copper sulfate and sulfuric acid.2+ The concentration of H2SO4 in the curing liquid is 30g / L, and the concentration of H2SO4 in the curing liquid is 200g / L; the pH value of the heat-resistant liquid is adjusted to 8 by using KOH, and the rolled copper foil after curing is placed in a heat-resistant tank containing the heat-resistant liquid for the third electrodeposition to obtain the rolled copper foil after heat-resistant treatment, and the current density of the third electrodeposition is 1A / dm 2 The temperature of the third electrodeposition is 50°C, the time of the third electrodeposition is 3s, the heat-resistant liquid is a mixture of potassium pyrophosphate and zinc sulfate, the concentration of K4P2O7 in the heat-resistant liquid is 40g / L, and the concentration of Zn in the heat-resistant liquid is 40g / L. 2+ The concentration of the anti-oxidation solution is 1g / L; the pH value of the anti-oxidation solution is adjusted to 10 by using KOH, and the rolled copper foil after the heat-resistant treatment is placed in the anti-oxidation tank containing the anti-oxidation solution for the fourth electrodeposition to obtain the anti-oxidation treated rolled copper foil, and the current density of the fourth electrodeposition is 3A / dm 2 , the temperature of the fourth electrodeposition is 25° C., the time of the fourth electrodeposition is 3 s, the anti-oxidation liquid is a mixture of potassium dichromate and potassium hydroxide, and the concentration of chromium ions in the anti-oxidation liquid is 1 g / L; the rolled copper foil after the anti-oxidation treatment is subjected to plasma treatment to obtain a plasma-treated rolled copper foil, the power of the plasma treatment is 10 W, the time of the plasma treatment is 60 s, the gas for the plasma treatment is an Ar / O2 mixed gas, and the volume ratio of argon to oxygen in the Ar / O2 mixed gas is 5: 1. The radio frequency power of the plasma treatment is 13.56 MHz; the pH value of the silane coupling agent solution is adjusted to 3 by using acetic acid, the silane coupling agent solution is sprayed on the surface of the rolled copper foil after the plasma treatment, and then the surface is dried by cold air, and the temperature of the cold air is 20° C. to obtain a pretreated rolled copper foil, the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.1 wt%, and the ratio of the mass of the silane coupling agent in the silane coupling agent solution to the surface area of the rolled copper foil is 0.0015 g:60 cm 2 The silane coupling agent is a combination of glycidyloxypropyl trimethoxysilane and aminopropyl triethoxysilane, and the mass ratio of glycidyloxypropyl trimethoxysilane to aminopropyl triethoxysilane is 0.1:1. The solvent in the silane coupling agent solution is a mixture of ethanol and water, and the volume ratio of ethanol to water is 2:1. The epoxy resin solution and the curing agent solution are sprayed on the surface of the pretreated rolled copper foil in sequence, and the sprayed rolled copper foil is hot-air dried and vacuum dried in sequence to obtain a surface-treated rolled copper foil, wherein the mass concentration of the epoxy resin in the epoxy resin solution is 2wt%, the mass concentration of the curing agent in the curing agent solution is 2wt%, and the ratio of the mass of the epoxy resin in the epoxy resin solution to the surface area of the rolled copper foil is 0.03g:60cm 2The mass ratio of epoxy resin to curing agent is 10:1. The epoxy resin solution is a dimer acid modified epoxy resin solution with a model of SQE-172. The curing agent solution is a triethylenetetramine solution. The solvents in the epoxy resin solution and the curing agent solution are both ethanol. The hot air drying temperature is 150°C; the hot air drying time is 10s, the vacuum drying temperature is 100°C, and the vacuum drying time is 12h.
[0049] Example 2
[0050] The difference from Example 1 is that the mass concentration of epoxy resin in the epoxy resin solution is 10wt%, the mass concentration of curing agent in the curing agent solution is 10wt%, and the ratio of the mass of epoxy resin in the epoxy resin solution to the surface area of the rolled copper foil is 0.3g:60cm 2 , and finally the surface treated rolled copper foil is obtained.
[0051] Example 3
[0052] The difference from Example 1 is that the mass concentration of epoxy resin in the epoxy resin solution is 0.1wt%, the mass concentration of curing agent in the curing agent solution is 0.1wt%, and the ratio of the mass of epoxy resin in the epoxy resin solution to the surface area of the rolled copper foil is 0.002g:60cm 2 , and finally the surface treated rolled copper foil is obtained.
[0053] Example 4
[0054] The difference from Example 1 is that the epoxy resin solution is a diphenylmethane diisocyanate solution with a model of SQE-140, and the curing agent solution is a diethylenetriamine solution, and finally a surface-treated rolled copper foil is obtained.
[0055] Example 5
[0056] The difference from Example 1 is that the power of the plasma treatment is 100 W, the time of the plasma treatment is 10 s, the volume ratio of argon to oxygen in the Ar / O2 mixed gas is 9:1, and finally a surface-treated rolled copper foil is obtained.
[0057] Example 6
[0058] The difference from Example 1 is that the power of the plasma treatment is 110 W, the time of the plasma treatment is 5 s, the volume ratio of argon to oxygen in the Ar / O2 mixed gas is 10:1, and finally a surface-treated rolled copper foil is obtained.
[0059] Example 7
[0060] The difference from Example 1 is that the mass concentration of the silane coupling agent in the silane coupling agent solution is 1wt%, and the ratio of the mass of the silane coupling agent in the silane coupling agent solution to the surface area of the rolled copper foil is 0.03g:60cm 2 , the pH value of the silane coupling agent solution was 5, and finally a surface treated rolled copper foil was obtained.
[0061] Example 8
[0062] The difference from Example 1 is that the mass concentration of the silane coupling agent in the silane coupling agent solution is 0.05wt%, and the ratio of the mass of the silane coupling agent in the silane coupling agent solution to the surface area of the rolled copper foil is 0.0010g:60cm 2 , the pH value of the silane coupling agent solution was 6, and finally the surface treated rolled copper foil was obtained.
[0063] Example 9
[0064] The difference from Example 1 is that the mass ratio of glycidyloxypropyltrimethoxysilane to aminopropyltriethoxysilane is 1:0.1, and the volume ratio of ethanol to water is 5:1, and finally a surface-treated rolled copper foil is obtained.
[0065] Example 10
[0066] The difference from Example 1 is that the mass ratio of glycidyloxypropyltrimethoxysilane to aminopropyltriethoxysilane is 1:0.01, and the volume ratio of ethanol to water is 6:1, and finally a surface-treated rolled copper foil is obtained.
[0067] Embodiment 11
[0068] The difference from Example 1 is that the current density of the first electrodeposition is 50A / dm 2 The first electrodeposition temperature is 30°C, the first electrodeposition time is 3s, and the Cu content in the roughening solution is 2+ The concentration of H2SO4 in the roughening solution is 100 g / L, and the current density of the second electrodeposition is 40 A / dm 2 The temperature of the second electrodeposition is 30°C, the time of the second electrodeposition is 10s, and the Cu content in the solidified liquid is 2+ The concentration of H2SO4 in the solidifying liquid is 100g / L, and finally the surface treated rolled copper foil is obtained.
[0069] Example 12
[0070] The difference from Example 1 is that the current density of the first electrodeposition is 18A / dm 2 The first electrodeposition temperature is 20°C, the first electrodeposition time is 2s, and the Cu content in the roughening solution is 2+The concentration of H2SO4 in the roughening solution is 95 g / L, and the current density of the second electrodeposition is 8 A / dm 2 The temperature of the second electrodeposition is 65°C, the time of the second electrodeposition is 2s, and the Cu in the solidified liquid is 2+ The concentration of H2SO4 in the solidifying liquid is 25g / L, and the concentration of H2SO4 in the solidifying liquid is 95g / L, and finally the surface treated rolled copper foil is obtained.
[0071] Example 13
[0072] The difference from Example 1 is that the pH value of the heat-resistant liquid is 11, and the current density of the third electrodeposition is 3A / dm 2 The temperature of the third electrodeposition is 30°C, the time of the third electrodeposition is 10s, the concentration of K4P2O7 in the heat-resistant liquid is 200g / L, and the Zn 2+ The concentration is 5 g / L; the pH value of the anti-oxidation solution is 13, and the current density of the fourth electrodeposition is 10 A / dm 2 The temperature of the fourth electrodeposition is 35° C., the time of the fourth electrodeposition is 10 s, the concentration of chromium ions in the anti-oxidation solution is 10 g / L, and finally a surface-treated rolled copper foil is obtained.
[0073] Embodiment 14
[0074] The difference from Example 1 is that the hot air drying temperature is 200° C.; the hot air drying time is 60 seconds, the vacuum drying temperature is 150° C., and the vacuum drying time is 6 hours, and finally a surface-treated rolled copper foil is obtained.
[0075] Embodiment 15
[0076] The difference from Example 1 is that the hot air drying temperature is 100° C.; the hot air drying time is 5 s, the vacuum drying temperature is 200° C., and the vacuum drying time is 2 h, and finally a surface-treated rolled copper foil is obtained.
[0077] Comparative Example 1
[0078] The difference from Example 1 is that the mass concentration of the epoxy resin in the epoxy resin solution is 15wt%, and finally a surface-treated rolled copper foil is obtained.
[0079] Comparative Example 2
[0080] The difference from Example 1 is that the plasma treatment is cancelled, and finally a surface-treated rolled copper foil is obtained.
[0081] Performance Testing
[0082] Roughness Rz: tested using the GB / T1031-2009 test standard.
[0083] Peel strength: tested using IPC-TM650 testing standard.
[0084] The surface treated rolled copper foils prepared in the examples and comparative examples were tested for roughness Rz and peel strength. The test results are shown in Table 1.
[0085] Table 1
[0086]
[0087]
[0088] Figure 1 This is the SEM image of the surface treated rolled copper foil in Example 1 of the present application, Figure 1 It can be seen that the copper teeth on the surface of the copper foil have a high spheroidization rate and the size of the copper teeth is below 300nm.
[0089] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0090] The present application involves pickling the rolled copper foil to remove oxides on the surface of the rolled copper foil. Roughening and curing treatments are performed to achieve the growth and stable existence of copper buds on the surface of the copper foil. Heat-resistant treatment is performed to form a zinc coating on the surface of the copper layer, which helps to block the thermal diffusion of copper ions and epoxy resin during heat treatment and improve the corrosion resistance of the rolled copper foil. Anti-oxidation treatment is performed to form a chromium-containing antioxidant film on the surface of the zinc coating, which helps to improve the corrosion resistance and oxidation resistance of the rolled copper foil. Plasma surface treatment increases the active oxygen-containing functional groups on the surface of the rolled copper foil, which helps to improve the interaction between the silanol groups and oxygen-containing functional groups of the silane coupling agent after hydrolysis, thereby helping to improve the bonding force between the rolled copper foil and the epoxy resin, and further helps to improve the peel strength of the rolled copper foil. At the same time, plasma surface treatment helps to increase the surface energy of the rolled copper foil and improve the spreading and infiltration of the silane coupling agent treatment solution in the pores of the copper buds. Coating the epoxy resin solution on the surface of the pre-treated rolled copper foil and controlling the mass concentration of the epoxy resin in the epoxy resin solution within the above range helps to pre-fill the epoxy resin solution between the copper bud particles, enhance the penetration of the epoxy resin between the copper bud particles, increase the contact area between the epoxy resin and the copper bud, and increase the peel strength of the rolled copper foil through mechanical interlocking between the epoxy resin and the copper bud particles. At the same time, the hydrophobic end of the silane coupling agent and the epoxy resin molecules are entangled with each other, which helps to enhance the interaction force between the molecules, thereby helping to further enhance the peel strength of the rolled copper foil.
[0091] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A surface treatment method for rolled copper foil, characterized in that: The surface treatment method comprises: Step S1, sequentially performing pickling, roughening, curing, heat-resistant, anti-oxidation, and plasma treatment on the rolled copper foil; sequentially performing silane coupling agent solution coating and first curing on the rolled copper foil after the plasma treatment to obtain a pretreated rolled copper foil; Step S2, sequentially coating the pretreated rolled copper foil with an epoxy resin solution, coating with a curing agent solution and performing a second curing to obtain a surface-treated rolled copper foil; wherein the mass concentration of the epoxy resin in the epoxy resin solution does not exceed 10wt%.
2. The surface treatment method according to claim 1, characterized in that: The ratio of the mass of the epoxy resin in the epoxy resin solution applied to the surface area of the rolled copper foil is 0.03-0.3 g:60 cm 2 ; and / or, the ratio of the mass of the epoxy resin in the applied epoxy resin solution to the mass of the curing agent in the curing agent solution is 10:1; Preferably, the epoxy resin solution is a dimer acid-modified epoxy resin solution or a diphenylmethane diisocyanate-modified epoxy resin solution; And / or, the curing agent solution is a triethylenetetramine solution or a diethylenetriamine solution.
3. The surface treatment method according to claim 1 or 2, characterized in that: The mass concentration of the epoxy resin in the epoxy resin solution is 2 to 10 wt %; and / or the mass concentration of the curing agent in the curing agent solution is 2 to 10 wt %.
4. The surface treatment method according to any one of claims 1 to 3, characterized in that: The power of the plasma treatment is 10 to 100 W; and / or the time of the plasma treatment is 10 to 60 s; And / or, the gas for plasma treatment is an oxygen-containing gas; preferably, the oxygen-containing gas is an Ar / O2 mixed gas or air; further preferably, the volume ratio of argon to oxygen in the Ar / O2 mixed gas is 5 to 9:
1.
5. The surface treatment method according to any one of claims 1 to 4, characterized in that: The mass concentration of the silane coupling agent in the silane coupling agent solution is 0.1-1 wt %; and / or, the ratio of the mass of the silane coupling agent in the coated silane coupling agent solution to the surface area of the rolled copper foil is 0.0015-0.03 g:60 cm 2 ; And / or, the pH value of the silane coupling agent solution is 3 to 5; And / or, the silane coupling agent is selected from any one or more of glycidyloxypropyltrimethoxysilane, aminopropyltriethoxysilane, 3-(trimethoxysilyl)propyl methacrylate and (3-mercaptopropyl)trimethoxysilane; Preferably, the silane coupling agent is a combination of glycidyloxypropyl trimethoxysilane and aminopropyl triethoxysilane, and the mass ratio of the glycidyloxypropyl trimethoxysilane to the aminopropyl triethoxysilane is 0.1-1:0.1-1; And / or, the solvent in the silane coupling agent solution is a mixture of ethanol and water, and the volume ratio of the ethanol to the water is 2 to 5:
1.
6. The surface treatment method according to any one of claims 1 to 5, characterized in that: The pickling comprises: placing the rolled copper foil in a sulfuric acid solution for immersion to obtain the pickled rolled copper foil; And / or, the volume concentration of sulfuric acid in the sulfuric acid solution is 10-15%; And / or, the soaking temperature is 20-30° C.; and / or, the soaking time is 10-30 seconds.
7. The surface treatment method according to any one of claims 1 to 6, characterized in that: The roughening treatment comprises: placing the pickled rolled copper foil in a roughening tank containing a roughening liquid to perform a first electrodeposition to obtain a roughened rolled copper foil; And / or, the current density of the first electrodeposition is 20 to 50 A / dm 2 ; and / or, the temperature of the first electrodeposition is 25 to 30° C.; and / or, the time of the first electrodeposition is 3 to 10 s; And / or, the roughening solution is a mixture of copper sulfate and sulfuric acid, wherein Cu 2+ The concentration of H2SO4 in the roughening solution is 10-30 g / L; and / or the concentration of H2SO4 in the roughening solution is 100-200 g / L.
8. The surface treatment method according to any one of claims 1 to 7, characterized in that: The curing treatment comprises: placing the roughened rolled copper foil in a curing tank containing a curing liquid to perform a second electrodeposition to obtain the cured rolled copper foil; And / or, the current density of the second electrodeposition is 10 to 40 A / dm 2 ; and / or, the temperature of the second electrodeposition is 30 to 60° C.; and / or, the time of the second electrodeposition is 3 to 10 s; And / or, the solidifying liquid is a mixture of copper sulfate and sulfuric acid, wherein Cu 2+ The concentration of H2SO4 in the solidifying liquid is 100-200 g / L.
9. The surface treatment method according to any one of claims 1 to 8, characterized in that: The heat-resistant treatment comprises: placing the rolled copper foil after the curing treatment in a heat-resistant tank containing a heat-resistant liquid to perform a third electrodeposition to obtain the rolled copper foil after the heat-resistant treatment; And / or, the current density of the third electrodeposition is 1 to 3 A / dm 2 ; and / or, the temperature of the third electrodeposition is 30 to 50° C.; and / or, the time of the third electrodeposition is 3 to 10 s; And / or, the heat-resistant liquid is a mixture of potassium pyrophosphate and zinc sulfate, and the concentration of K4P2O7 in the heat-resistant liquid is 40-200 g / L; and / or, the concentration of Zn in the heat-resistant liquid is 2+ The concentration is 1 to 5 g / L; and / or the pH value of the heat-resistant liquid is 8 to 11; And / or, the anti-oxidation treatment comprises: placing the rolled copper foil after the heat-resistant treatment in an anti-oxidation tank containing an anti-oxidation liquid to perform a fourth electrodeposition to obtain the anti-oxidation treated rolled copper foil; And / or, the current density of the fourth electrodeposition is 3 to 10 A / dm 2 ; and / or, the temperature of the fourth electrodeposition is 25 to 35° C.; and / or, the time of the fourth electrodeposition is 3 to 10 s; And / or, the anti-oxidation liquid is a mixture of potassium dichromate and potassium hydroxide, and the concentration of chromium ions in the anti-oxidation liquid is 1-10 g / L; and / or, the pH value of the anti-oxidation liquid is 10-13.
10. The surface treatment method according to any one of claims 1 to 9, characterized in that: The second curing comprises hot air drying and vacuum drying performed sequentially; And / or, the hot air drying temperature is 150-200°C; and / or, the hot air drying time is 10-60s; And / or, the vacuum drying temperature is 100-150° C.; and / or, the vacuum drying time is 6-12 hours.
Citation Information
Cited By
Rolled copper foil for current collector of lithium ion battery and preparation method of rolled copper foil
CN120989614A